Students’ Mathematical Problem Solving Ability and Disposition using Contextual Teaching and Learning Approach - Rippi Maya; Siti Ruqoyyah ((JIML) JOURNAL OF INNOVATIVE MATHEMATICS LEARNING, 2021)
The aim of this study is to analyze the role of Contextual Teaching and Learning (CTL) approach on students’ mathematical problem solving ability (MPSA) and disposition (MD). The study is a pre-test post-test experimental control group design, that involved 40 tenth grade students of a Madrasah Aliyah (MA) in Bandung, that were chosen by purposive sampling technique. The instrumens used in this study consisted a mathematical problem solving test (4 essays) and a mathematical disposition scale (26 statements). The study found that on MPSA, its normalized Gain and on MD, students getting treatment with CTL attained better grades than grades of students taught by conventional teaching. Even though both students’ grades on MPSA were still at a very low level, but on MD, first group students’ grade on MD was at a medium level and the second group students’ grade was at a low level. Many students still experiencing difficulties on compiling MPSA. The other findings, there was no association between MPSA and MD, but students performed good perception toward CTL approach.